Analogue and Numerical Modelling of Sedimentary Systems: From Understanding to Prediction 2008
DOI: 10.1002/9781444303131.ch1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Syn‐ to Post‐Depositional History of a Prograding Carbonate Platform: The Rosengarten, Middle Triassic, Dolomites, Italy

Abstract: A combination of thermal history, numerical basin-reverse and sequence-stratigraphic forward modelling is applied to the Mesozoic outcrop analogue of the Rosengarten carbonate platform area in the Dolomites of northern Italy. This integrated multidisciplinary approach of numerical simulation quantifies the thermal, subsidence, geometrical and subsequent facies evolution of the area. Calibration data during modelling were vitrinite reflectance (VR) and apatite fission-track (FT) analyses as well as detailed out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 69 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…Sample coverage of maturity measurements by selected previous publications (Tscherny 2006;Emmerich et al 2008;Blendinger et al 2013) is shown in Fig. 1.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample coverage of maturity measurements by selected previous publications (Tscherny 2006;Emmerich et al 2008;Blendinger et al 2013) is shown in Fig. 1.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…In four samples neither vitrinites nor solid bitumen has been detected (13/643, 13/688, 13/710 and 13/711). New obtained data (this study) were compared to literature data from other parts of the Dolomites (Buggisch 1978;Schulz and Fuchs 1991;Bielefeld 1998;Tscherny 2006;Emmerich et al 2008;Blendinger et al 2013). Thus, a total number of 75 samples with vitrinite reflectance values is available (''Appendix Table 4'').…”
Section: Organic Petrologymentioning
confidence: 99%
See 2 more Smart Citations
“…Several Triassic carbonate platforms in the Dolomites, northern Italy, (Figure 1) are considered outcrop analogues for subsurface (dolomite) hydrocarbon reservoirs, for instance the Sella Group (Antonellini and Mollema, 2000), Pale di San Lucano (Blendinger and Meissner, 2006) and the Rosengarten or Catinaccio (Emmerich et al, 2009). Also in the Latemar, several aspects, such as platform geometry and fracturing, are covered in the literature as outcrop analogues.…”
Section: Geological Settingmentioning
confidence: 99%